Оптимальный выбор стандартных несущих конструкций для электронных средств - Efimenko, A. A.; Vil’chinskiy, A. I. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
Models and algorithms of choosing the standard load-carrying structures allowing to optimize development process of electronic devices are offered.